Дисбиотические осложнения в желудке крыс при антихеликобактерной терапии и их профилактика кверцитин-содержащими препаратам - Гоженко, А.И.; Шухтина, И.Н.; Петренко, А.А. (Актуальні проблеми транспортної медицини, 2015)
У крыс, которые получали антихеликобактерную терапию (АХБТ) в течение 8 дней, в желудке развивался дисбактериоз и гастрит, которые можно было предотвратить кверцетинсодержащими препаратами «Квертулин» и «Квертулидон». У щурів, які отримували антихелікобактерну терапію (АХБТ) протягом 8 днів, в шлунку розвивався дисбіоз і гастрит, які можливо попередити кверцетин-вмісними препаратами «Квертулін» або «Квертулідон» Aim: To establish a pro-dysbiotic effect of anti-helicobacter pylori therapy (AHBT) on the stomach and identify preventive effectiveness of quercetincontaining drugs. Materials and methods: The rats have received AHBT (omeprazole 1.3 mg/kg, amoxil 50 mg/kg and clarithromycin 7.5 mg/kg) daily for 8 day; and oral applications of quercetin-containing gels “Quertulin” (quercetin + inulin + calcium citrate) or “Qertulidon” (qertulin + imudon) for 11 days. After euthanasia of animals on day 12 there were determined leukocytes levels and leukocyte formula in the blood, and the activity of urease, lysozyme, catalase, pepsin and content of malondialdehyde (MDA) in the homogenate of the gastric mucosa. Prooxidant-antioxidant index (PAI) was calculated as the ratio of the catalase activity and MDA content, the degree of dysbiosis by Levitsky was calculated as the ratio of the relative activities of urease and lysozyme. Results: AHBT reduces neutrophils and increases the portion of lymphocytes by 1.5 times in the blood. AHBT also increases urease activity by 2.5 times and reduces the lysozyme activity by 2-fold, which gives the 5-fold increase in the degree dysbiosis in the gastric mucosa. This increases the elastase level (a marker of inflammation) and reduces PAI. Quercetin-containing drugs, especially Qertulidon, show a protective effect. Conclusion: AHBT causes the development of dysbiosis and gastritis, which can be prevented by oral applications with quercetin-containing gels.